Restorative Justice Against Child Crime In the Perspective of Islamic Law at the Bengkulu City Police Station - Prakoso, Arie Putra; Yunus, Fatimah; Sitorus, Iwan Romadhan (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstracts: This study raises the issue of the process of restorative justice in crimes committed by children at the Bengkulu City Police and the perspective of Islamic law on the application of restorative justice to juvenile crimes. To answer this problem, empirical juridical research was used with direct interviews with investigators on the protection of women and children (PPA) at the Bengkulu City Police. After the data can then be analyzed based on normative descriptive analysis. The results of the study show that: (1) The process of implementing restorative justice for crimes committed by children at the Bengkulu City Police can be carried out in 2 ways; (a) restorative justice can be carried out outside the police office. (b) Restorative justice can be carried out at the police office. (2) The application of restorative justice to juvenile crimes in the perspective of Islamic law prioritizes peace or forgiveness through mediation, reconciliation between perpetrators, victims, law enforcers and the wider community directly participating in solving problems. Islamic law is aligned in law enforcement against children who are in conflict with the law.Keywords: Restorative Justice and Child Crime Abstrak : Penulisan menjelaskan tentang proses restoratif justice pada tindak pidana yang dilakukan anak di Polresta Kota Bengkulu dalam perspektif hukum Islam. Untuk menjawab permasalahan ini digunakan penelitian yuridis empiris dengan wawancara secara langsung kepada penyidik perlindungan perempuan dan anak (PPA) pada Polresta Kota Bengkulu. Hasil penelitian menunjukan bahwa: (1) Proses pelaksanaan restoratif justice pada tindak pidana yang dilakukan anak di Polresta Kota Bengkulu dapat dilakukan 2 cara;(a) restorative justice dapat dilakukan di luar. (b) Restorative justice dapat dilakukan di kantor kepolisian.(2) Penerapan restoratif justice terhadap tindak pidana anak dalam perspektif hukum Islam lebih mendepankan perdamaian atau pemaafan dengan mediasi, rekonsliasi antara pelaku, korban, para penegak hukum dan masyarakat luas ikut secara langsung berpartisipasi dalam menyelsaikan permasalahan. Hukum Islam selaras dalam penegakan hukum terhadap anak yang berhadapan dengan hukum.Kata kunci: Restoratif Justice dan Tindak Pidana Anak